The impact of digital transformation on green technology innovation in manufacturing enterprises: Empirical evidence based on text analysis - Zhang, Fang; Tian, Haoheng; Huang, Lijia; Sun, Xia (Edelweiss Applied Science and Technology, 2025)
The research investigates how digital evolution affects innovation in eco-friendly technology within A-share listed manufacturing companies between 2010 and 2022. Employing textual examination to derive terms associated with "digital transformation" from yearly summaries, the study evaluates the extent of digitization in businesses. Findings indicate a substantial enhancement in green technology innovation due to digital transformation, with financial and economic development levels acting as mediators. Heterogeneity analysis reveals that the impact varies by ownership structure, financial market environment, and executive shareholding. This research proposes strategies to boost innovation in green technology via digital transformation, aiding in the sustainable growth of China’s manufacturing industry.